The nexus of biofuels, climate change, and human health : workshop summary - Pool, Robert; Institute of Medicine (U.S.); Institute of Medicine (U.S.). Roundtable on Environmental Health Sciences, Research, and Medicine (National Academies Press, 2014)
"In January 2013, the Roundtable on Environmental Health Sciences, Research, and Medicine of the Institute of Medicine held a 2-day, interactive, public workshop on the intersection of biofuels, climate change, and human health. Workshop attendees explored public health issues related to the composition of traditional and alternative fuels and fuel additives, and they discussed the known and potential health impacts associated with the use of these fuels and fuel additives. The Nexus of Biofuels, Climate Change, and Human Health is the summary of that workshop. This report examines air, water, land use, food, and social impacts of biomass feedstock as an energy resource, and the state of the science and health policy implications of using different types (and generations) of biofuels as an energy source."--
Keywords: Biomass energy : Climatic factors : Congresses; Biomass energy : Health aspects : Congresses